Characteristics of Stimulus Intensity in Transcutaneous Vagus Nerve Stimulation for Chronic Tinnitus - Suk, Won Choi (J Int Adv Otol, 2018)
OBJECTIVES: We aimed to assess the clinical significance of the intensity of transcutaneous vagus nerve stimulation (tVNS) in chronic tinnitus. MATERIALS AND METHODS: Four sessions of tVNS were performed over a 2-week period for 24 patients with unilateral, non-pulsatile chronic tinnitus. The cavum, cymba, and tragus were sequentially stimulated to the maximal sensory thresholds. One month later, after the four sessions, the level of tinnitus distress and changes in stimulus intensity were assessed. RESULTS: The stimulus intensity did not differ according to sex or laterality. However, a moderate positive correlation between tinnitus distress and the initial stimulus intensity was observed. This correlation was not observed during the subsequent sessions. The stimulus intensity at the cavum changed significantly (p=0.018), and notable differences in tinnitus annoyance were observed between the responders and non-responders (p=0.006). CONCLUSION: The effect of stimulus intensity on the treatment outcome seems to be limited. An increasing trend in the stimulus intensity for tinnitus annoyance at the cavum was observed in the responders. Therefore, the cavum may be an optimal stimulation site for tVNS.